2013
DOI: 10.1111/ene.12073
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke at a young age is a serious event – final results of a population‐based long‐term follow‐up in Western Norway

Abstract: Our data show a heterogeneous prognosis and high mortality even for long-time survivors of ischaemic stroke at a young age. Prospective studies of young stroke patients and controls are necessary for direct comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 22 publications
5
59
2
1
Order By: Relevance
“…4,28 In our study, factors associated with mortality during the follow-up are similar to previous ones because our analysis showed that increasing age, active malignancy, type 1 diabetes mellitus, heart failure, heavy drinking, stroke in multiple territories, and increasing NIHSS score are associated with long-term mortality at young age. 9,10,29 About stroke pathogenesis, those with stroke because of large-artery atherosclerosis experienced a strikingly high cumulative 17-year mortality rate (60%) and the highest SMR (17.08) and absolute excess . Also their multivariable hazard (13.58 compared with internal carotid artery dissection patients) was among the highest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,28 In our study, factors associated with mortality during the follow-up are similar to previous ones because our analysis showed that increasing age, active malignancy, type 1 diabetes mellitus, heart failure, heavy drinking, stroke in multiple territories, and increasing NIHSS score are associated with long-term mortality at young age. 9,10,29 About stroke pathogenesis, those with stroke because of large-artery atherosclerosis experienced a strikingly high cumulative 17-year mortality rate (60%) and the highest SMR (17.08) and absolute excess . Also their multivariable hazard (13.58 compared with internal carotid artery dissection patients) was among the highest.…”
Section: Discussionmentioning
confidence: 99%
“…If no visible ischemic lesion was present but symptoms lasted for 24 hours, lesion size was considered small. 18 Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) both as a total score at admission and as divided into mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14), and severe (≥15). 19 The classification of stroke pathogenesis was done independently by pairs of investigators, reaching consensus when necessary.…”
Section: Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation
“…13 Due to the large proportion of cryptogenic events, the evidence base to guide prevention and treatment of early-onset IS remains poor. Nevertheless, several studies show high rates of recurrent stroke and to lesser extent other cardiovascular disease in the young suggesting active underlying pathologies, [14][15][16] also for those with undetermined causes. 17 To address the many gaps in this field and promote the understanding of risk factors, mechanisms and prognosis of early-onset cryptogenic IS, we generated the following study hypotheses:…”
Section: Introductionmentioning
confidence: 99%
“…In young adults, the definition of young ranges from 16 to 45 years, as in our study, to 18 to 55 years. Moreover, the few studies reporting long-term outcome in young adults are either based on a retrospective selection of patients, 24 which carries the risk of a selection bias, or use other outcome measures than the mRS. 11 In the prospective Follow-Up of Transient Ischemic Attack and Stroke Patients and Unelucidated Risk Factor Evaluation (FUTURE) study, the detailed comparison of the distribution of mRS scores reveals results that are similar to ours (mRS 0-1 in 46%, according to figure C in the cited article, compared to 55% in our study). 25 Little is known about psychosocial disturbances after AIS in young patients, particularly in children.…”
mentioning
confidence: 99%